Psychological cognition and women's entrepreneurship: A country-based comparison using fsQCA - Yangjie Huang; Mengting Zhang; Jing Wang; Ping Li; Kexin Li (Journal of Innovation & Knowledge (JIK), 2022)
Entrepreneurial activity measures a country's economic vitality. Studies have examined the psychological cognitive conditions that influence women's entrepreneurial activity by considering the effects of individual psychological cognitive conditions in isolation while ignoring their interdependence. Based on the necessary condition analysis and the fuzzy-set qualitative comparative analysis, this study utilized data from the 2021 Global Entrepreneurship Monitor report for 42 countries and explored the complex causal mechanisms driving women's entrepreneurial activity. We observed that (1) a single psychological cognitive factor does not constitute a necessary condition for high female entrepreneurial activity (FEA), despite high entrepreneurial expectation and capability perception (CP); (2) the driving mechanisms for high and low FEA can be categorized into three and four pathways, respectively. There is an asymmetric relationship between the driving paths of high and low FEA. Finally, we propose three measures to support female entrepreneurship: optimizing female psychological cognition, improving female CP, and establishing excellent female entrepreneurial role models.
Keywords: J16; M13; O38; 650; Entrepreneurial activity; Female entrepreneurship; fsQCA; NCA; Psychological cognition